2023
DOI: 10.3390/ijms24031945
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Promyelocytic Leukemia Zinc Finger (PLZF) and Glial-Derived Neurotrophic Factor Family Receptor Alpha 1 (GFRα1) in the Cryopreservation of Spermatogonia Stem Cells

Abstract: The cryopreservation of spermatogonia stem cells (SSCs) has been widely used as an alternative treatment for infertility. However, cryopreservation itself induces cryoinjury due to oxidative and osmotic stress, leading to reduction in the survival rate and functionality of SSCs. Glial-derived neurotrophic factor family receptor alpha 1 (GFRα1) and promyelocytic leukemia zinc finger (PLZF) are expressed during the self-renewal and differentiation of SSCs, making them key tools for identifying the functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 220 publications
0
1
0
Order By: Relevance
“…To determine the role of riluzole in the differentiation of spermatogonia, we examined the expressions of GFRα1, PCNA, SYCP3, and TNP-1, key markers involved in spermatogonia proliferation and differentiation. Our findings revealed that a significant decrease in the expression levels of GFRα1 (which is associated with the self-renewal of SSCs (Shamhari et al, 2023)), PCNA (a marker for proliferating cell nuclear antigen (Fu et al, 2019)), SYCP3 (involved in meiosis (Miyamoto et al, 2003)), and TNP-1 (specific to spermatids (Della-Maria, Gerard, Franck, & Gerard, 2002)) after BSF treatment. However, treatment with riluzole, whether administered via intraperitoneal injection or intragastric gavage, significantly increased the expression of these marks (Figure 3A-D).…”
Section: Resultsmentioning
confidence: 78%
“…To determine the role of riluzole in the differentiation of spermatogonia, we examined the expressions of GFRα1, PCNA, SYCP3, and TNP-1, key markers involved in spermatogonia proliferation and differentiation. Our findings revealed that a significant decrease in the expression levels of GFRα1 (which is associated with the self-renewal of SSCs (Shamhari et al, 2023)), PCNA (a marker for proliferating cell nuclear antigen (Fu et al, 2019)), SYCP3 (involved in meiosis (Miyamoto et al, 2003)), and TNP-1 (specific to spermatids (Della-Maria, Gerard, Franck, & Gerard, 2002)) after BSF treatment. However, treatment with riluzole, whether administered via intraperitoneal injection or intragastric gavage, significantly increased the expression of these marks (Figure 3A-D).…”
Section: Resultsmentioning
confidence: 78%
“…Infertility affects approximately 30% of males and 70% of females [11]. Various problems, such as ovulatory (25%), tubular (15%), and uterine (5%) factors, cause FI, and 25% of cases remain unexplained [12]. PCOS is a major factor contributing to the development of FI [13].…”
Section: Introductionmentioning
confidence: 99%